2011
DOI: 10.1103/physrevb.84.195201
|View full text |Cite
|
Sign up to set email alerts
|

Compensation-doped silicon for photovoltaic applications

Abstract: A small overlap between the silicon optical absorption spectrum and the solar spectral irradiance limits the conversion efficiency of crystalline thin-film silicon solar cells. In this work, a theoretical search for compensation-doped silicon is carried out aiming to maximize the spectral overlap. First, a wide range of dopant species and concentrations is considered using the virtual crystal approximation and the empirical pseudopotential method. Second, the most promising modifications of silicon are investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Beyond a certain doping level, the cubic phase is likely to dominate. This is what Samsonidze et al [22] observed in the case of Si-group. They doped CoVSi, CoNbSi, and CoTaSi by Sn until they obtained the stable cubic symmetry.…”
Section: B Structural Optimizationsupporting
confidence: 73%
See 1 more Smart Citation
“…Beyond a certain doping level, the cubic phase is likely to dominate. This is what Samsonidze et al [22] observed in the case of Si-group. They doped CoVSi, CoNbSi, and CoTaSi by Sn until they obtained the stable cubic symmetry.…”
Section: B Structural Optimizationsupporting
confidence: 73%
“…In a recent first-principles based search of new TE prospects, 18-VEC orthorhombic systems CoVSi, CoNbSi, and CoTaSi were doped with Sn [22]. Beyond a certain doping level, the cubic phase was found to be the ground state, i.e., favorable for thermoelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of III-V elements into Si has been recently proposed as a way to enhance the absorption by direct optical transitions. 20 Our method accomplishes this goal using an elegant approach that reaches the maximum possible concentration of isolated "donor-acceptor" pairs within fully interlinked III-V-(IV) 3 building blocks (see Fig. 1) in a diamond-structure matrix.…”
Section: Introductionmentioning
confidence: 99%
“…7,11 This is because about 93% of the energy in sunlight is concentrated in the visible and infrared light with wavelength (k) in the range of 390-4000 nm (corresponding to 0.31-3.18 eV); 12 however, E g of BFO is 2.67 eV, so that photons with k > 464 nm, which account for more than 85% of the total energy, cannot be absorbed. 13 To improve the optical absorption of BFO thin films, their bandgap needs to be narrowed. 13 An effective and economical way of bandgap engineering is strain, 4 including external stresses, such as uniaxial 14 or hydrostatic pressures, 15 or internal strains, such as chemical pressure or lattice mismatch.…”
mentioning
confidence: 99%
“…13 To improve the optical absorption of BFO thin films, their bandgap needs to be narrowed. 13 An effective and economical way of bandgap engineering is strain, 4 including external stresses, such as uniaxial 14 or hydrostatic pressures, 15 or internal strains, such as chemical pressure or lattice mismatch. 4 Strain engineering has been widely employed in semiconductors to acquire desirable electronic, mechanical, and other properties.…”
mentioning
confidence: 99%